Cardiac Denial and Psychological Predictors of Cardiac Care Adherence in Adults With Congenital Heart Disease. (January 2016) - White, Kamila S.; Pardue, Caleb; Ludbrook, Philip; Sodhi, Sandeep; Esmaeeli, Amirhossein; Cedars, Ari
The current study examined cardiac denial and psychological predictors (i.e., depression, anxiety) of health outcomes including medical nonadherence and physical health in a sample of 80 adults with congenital heart disease (ACHD). Results indicated that denial of impact was elevated in this patient group compared with reference groups, and denial was negatively associated with depression and anxiety at p s < .01. Results indicated that depression, anxiety, and denial predicted unique variance in medical nonadherence, and gender moderated the relationships between these psychological factors and nonadherence. For depression, men and women showed similar relationships between depression and nonadherence at high levels of depression; however, at low levels of depression (i.e., a more normal mood state), men were less adherent compared with women. For anxiety, men and women did not differ in adherence at low levels of anxiety; however, men experiencing high anxiety were less adherent compared with women experiencing high anxiety. Implications of this study are discussed including the role of gender and denial and the impact of denial functioning to reduce negative affect. Depression was the only significant predictor of physical functioning. Results of this study suggest that psychological interventions aimed at depression and anxiety may function differently across gender to improve patient medical adherence and improve physical functioning in ACHD.